2008
DOI: 10.1172/jci35754
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glycoprotein Ibα forms catch bonds with human WT vWF but not with type 2B von Willebrand disease vWF

Abstract: Arterial blood flow enhances glycoprotein Ibα (GPIbα) binding to vWF, which initiates platelet adhesion to injured vessels. Mutations in the vWF A1 domain that cause type 2B von Willebrand disease (vWD) reduce the flow requirement for adhesion. Here we show that increasing force on GPIbα/vWF bonds first prolonged ("catch") and then shortened ("slip") bond lifetimes. Two type 2B vWD A1 domain mutants, R1306Q and R1450E, converted catch bonds to slip bonds by prolonging bond lifetimes at low forces. Steered mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
431
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 234 publications
(466 citation statements)
references
References 59 publications
(108 reference statements)
30
431
4
1
Order By: Relevance
“…As mentioned previously, the characteristic timescale for vWF tE10 À 4 s, which implies that we expect the binding energy to be in between the lowest binding energy we have studied here of 4 k B T and the intermediate energy of 5 k B T. Along the reaction coordinate, the distance between the binding minima and the top of the barrier for the GPIba-vWF A1 pair has been experimentally measured to be B2 nm 28 . This gives a bond breakup force of the order of B10 pN that is in excellent agreement with experiments 28,29 .…”
Section: Discussionsupporting
confidence: 88%
“…As mentioned previously, the characteristic timescale for vWF tE10 À 4 s, which implies that we expect the binding energy to be in between the lowest binding energy we have studied here of 4 k B T and the intermediate energy of 5 k B T. Along the reaction coordinate, the distance between the binding minima and the top of the barrier for the GPIba-vWF A1 pair has been experimentally measured to be B2 nm 28 . This gives a bond breakup force of the order of B10 pN that is in excellent agreement with experiments 28,29 .…”
Section: Discussionsupporting
confidence: 88%
“…Nonequilibrium processes can be produced by mechanical perturbations such as force and flow. Indeed, a recent study has demonstrated that force slows off-rate of GPIb␣-VWF dissociation (an unusual characteristic called catch bonds), which underlies f lowenhanced platelet rolling on VWF and prevents platelet agglutination (21). GOF mutations in the A1 domain away from the binding site eliminate catch bonds, abolish the flow requirement for rolling, and cause platelet agglutination.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we find a complex mechanical regulation of adhesive bonds at the single-molecule level: tensile force prolongs the bond lifetime (that is, catch bonds). In contrast to the well-known catch bonds of bimolecular systems, such as cell adhesion receptors (integrins 28,38,39 , selectins 40,41 , glycoprotein Iba 30,42 , E-cadherin 43 and FimH 44 ), the T-cell receptor 31 and cytoskeletal linkages 45,46 , the Thy-1 catch bond is strongly correlated with a bond-stiffening phenotype, termed 'dynamic catch', which partially shifts force to the already engaged but unstretched coreceptor Syn4. Thus, the data reveal a unique, previously unreported class of receptor-ligand bonds whereby force tightens co-receptor engagement that is required for forcemediated adhesion signalling.…”
mentioning
confidence: 99%